Perturbations associated with hungry gut microbiome and postbiotic perspectives to strengthen the microbiome health - Simardeep Kaur; Steffy Kaur Thukral; Preetiman Kaur; Mahesh Kumar Samota (Future Foods, 2021)
The imbalance in intestinal microbiota has serious consequences in human disease development such as inflammatory bowel, cardiovascular disorders, type II diabetes, obesity, cancer, respiratory disorders, and behavioral Alzheimer's and Parkinson's diseases. Therefore, the exploration of therapeutic interventions for maintaining the healthy gut microbiome is essential. Although, prebiotics, probiotics, and synbiotics have been frequently used for modulating gut microbiome composition to healthier side. However, the presence of immunosuppressing organisms in probiotics imposes a risk (mainly associated with their intake). This provides the baseline for exploring another substitute group- ‘Postbiotics’. Postbiotics are non-viable metabolites, and the risks associated with their intake can be minimized as compared to probiotics. In this review, we discuss the development and perturbations associated with the gut microbiome, postbiotic classes, and pleiotropic effects, the efficacy of postbiotics in functional foods, and their potential future perspectives along with knowledge gaps.